Two New Species of Coeligetes Jacoby From Malaysia (Coleoptera, Chrysomelidae, Galerucinae) - Mohamed S. Mohamedsaid (Psyche: A Journal of Entomology)
Coeligetes borneensis, n.sp. and Coeligetes wilcoxi, n.sp. are described from Malaysia. The presence of the genus in Malaysia is a new vecordo A key to Malaysian species is provided.